2010
DOI: 10.1111/j.1365-2621.2010.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Original article: Effect of modified atmosphere packaging using different CO2 and N2 combinations on physical, chemical, microbiological and sensory changes of fresh sea bass (Dicentrarchus labrax) fillets

Abstract: The effect of different modified atmosphere packaging (MAPs) on physical, chemical, microbiological and sensory changes of sea bass fillets when stored at 4°C and standard light conditions was investigated for up to 21 days and compared to a control batch stored in overwrap. Sea bass fillets were packed using different CO 2 and N 2 combinations (40% CO 2 -60% N 2 ; 50% CO 2 -50% N 2 ; 60% CO 2 -40% N 2 ), and quality assessment was based on instrumental, chemical, microbiological and sensory analysis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
14
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
7
14
0
3
Order By: Relevance
“…TVC and psychrotrophic microorganisms followed a similar pattern. The initial counts were higher than those reported by some authors (Cakli et al, 2007;Hernández et al, 2009;Kostaki et al, 2009) but similar to those mentioned by others (Chouliara et al, 2004;Provincial et al, 2010), who reported initial total aerobic mesophilic counts of 4 log cfu g -1 .…”
Section: Microbiological Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…TVC and psychrotrophic microorganisms followed a similar pattern. The initial counts were higher than those reported by some authors (Cakli et al, 2007;Hernández et al, 2009;Kostaki et al, 2009) but similar to those mentioned by others (Chouliara et al, 2004;Provincial et al, 2010), who reported initial total aerobic mesophilic counts of 4 log cfu g -1 .…”
Section: Microbiological Analysissupporting
confidence: 85%
“…No significant differences were found in WHC in corvine samples Downloaded by[New York University] at 06:storage(Hernández et al, 2009). However, in our case, a noticeable significant difference (P<0.001) was obtained in C compared with V and MAP at seven days.Some researchers have shown that overwrap samples of seabass presented greater drip loss than MAP samples(Provincial et al, 2010). These results indicated a lower WHC of overwrap samples in relation to MAP samples, which agrees with our results.Álvarez et al (2012) also found an effect of storage on the values of WHC in seabream fillets kept in aerobiosis.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…It has been confirmed that fish packaging in modified atmosphere significantly extends the shelf life of the product (Masniyom et al 2002;Stamatis & Arkoudelos 2007;Provincial et al 2010). The most common freshwater fish retailed in the Serbia are carp.…”
mentioning
confidence: 86%
“…So, taking some measures to delay the decline of fish quality and extend the preservation life of fish during chilling is worthwhile. Many methods have been reported-such as high hydrostatic pressure (Erkan and Üretener, 2010), irradiation process , ozonized slurry ice (Campos et al, 2005), and modified atmosphere packaging (Aas et al 2010;Provincial et al, 2010). Previous studies have shown that edible coatings made of protein, polysaccharide, and oil-containing materials help to prolong the shelf life and preserve the edible quality attributes (Jeon et al, 2002;Fan et al, 2009;Gómez-Estaca et al, 2010).…”
Section: Introductionmentioning
confidence: 97%